الثنائية اللغوية في تعليم اللغة العربية - Qomari, Nur (UIN Syekh Wasil Kediri, Indonesia, 2018)
Bilingualism in teaching is something to be done to make the quality of teaching more effective especially in the World Class University Like Islamic State Of University Maulana Malik Ibrahim Malang. This Article will be give information about implementation of Bilingulism in teaching. And also give information about the definition of bilingual and what kind of bilingual can be implemented especially in Arabic language teaching for the foreigner. Beside of information about the kind of the suitable bilingual in teaching language, This Article also inform how much of Arabic language acquisition when that language to be tought by bilingual method. And offcourse this give information about the relationship between the bilingual teaching language with the skills of language.